Single-site laparoscopic ligation of the hernia sac in infants with congenital Morgagni hernia - Wang, Cao; Liu, Xiang; Shu, Zhen; Yin, Jia; Luo, Zheng; Zhou, Guangxu; Liu, Bin (Frontiers in Pediatrics, 2023)
Background: Congenital Morgagni hernia (CMH) is a rare midline defect involving herniation of abdominal viscera into the thoracic cavity through triangular parasternal gaps in the diaphragm. We describe three cases of CMH in infants. Methods: The medical records of three patients (males; age: 14 months, 30 months, 48 months) with CMH admitted to the Department of Pediatric Surgery at the Affiliated Hospital of Zunyi Medical University between 2018 and 2022 were retrospectively reviewed. Pre-operative diagnosis was based on chest X-ray, chest computerized tomography, and barium enema. All patients were treated with single site laparoscopic high ligation of the hernia sac. Results: Hernia repair was successful in all patients. The average operative time for repair of a unilateral hernia was 20±5 minutes. Volume of surgical blood loss was 2-3 ml. There was no damage to organs such as the liver or intestines, or to tissues such as the pericardium or the phrenic nerve. Patients were allowed a fluid diet 6-8 hours after surgery, and remained on bed rest until 16 hours after surgery. No postoperative complications occurred, and patients were discharged on postoperative Day 2 or 3. No symptoms or complications were noted during the 1–48 months of follow-up. Aesthetic outcomes were satisfactory. Conclusions: Single site laparoscopic high ligation of the hernia sac provides pediatric surgeons a safe and effective technique for repair of CMH in infants and children. The procedure is straightforward, operative time and surgical blood loss are minimal, recurrence is unlikely, and aesthetic outcomes are satisfactory.